Motor coordination of eye-foot and ear-foot in adolescents: a comparison between adolescents engaged in rhythmic sports and ball sports - Ravisara Trongjitpituk (Human Movement)
Purpose Motor coordination is essential for physical fitness and effective participation in sports. Various sports emphasise different types of coordination, with rhythmic sports focusing on timing and synchronisation and ball sports on quick reactions and precision. This study examines the impact of participation in rhythmic and ball sports on eye-foot and ear-foot coordination in adolescents.